THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING SCHOOL ADMINISTRATION MANAGEMENT - Erna Widyasari; Harsono Harsono; Suyatmini Suyatmini; Al-Amin (Adisam Publisher, 2025)
The rapid development of information technology (IT) has redefined the way schools manage their resources and administrative processes. The purpose of this study is to analyze the role of IT in improving administrative management in schools and identify its significant impact on the efficiency of school organizations. The research method used in this study is the literature method. The results of this study show that IT plays a crucial role in easing the daily operations of schools, such as automated attendance, scheduling, financial administration and student performance tracking. The use of SIS has provided a strong foundation for schools to manage big data more effectively, facilitating data-driven decision-making and transparency in communication. Furthermore, the LMS and online collaboration tools have improved communication between staff, students and parents, enabling a more inclusive and responsive learning environment. Despite significant improvements, challenges related to data privacy, cybersecurity, as well as the need for proper training for staff remain obstacles.